GABA-A receptors play a minor role in cortical epileptic afterdischarges in immature rats - Tabashidze, N; Mareš, P (Brain research, 2011)
The role of inhibitory γ-aminobutyric acid-A (GABA-A) system in the cortical epileptic afterdischarges (ADs) was studied at three different developmental stages of rats. Animals 12, 18 and 25days old with implanted epidural electrodes were pretreated with bicuculline (1 and 2mg/kgi.p.) and 15min later repeatedly stimulated with low frequency trains with stepwise increasing current intensity. Bicuculline only exceptionally decreased threshold current intensities necessary for elicitation of movements directly bound to stimulation, spike-and wave ADs, clonic seizures and transition into a limbic type of ADs. Duration of ADs was not systematically affected by either dose of bicuculline. In contrast, transcallosal evoked potentials exhibited under the influence of bicuculline steeper curve expressing relation between intensity of stimuli and amplitude of responses. In contrast to GABA-B receptors, GABA-A receptors do not play an important role in generation and arrest of cortical epileptic ADs in immature rats.
Keywords: Receptors, GABA-A; Animals; elektrická stimulace; Electric Stimulation; bikukulin; receptory GABA-A; Rats, Wistar; Seizures; Electrodes, Implanted; GABA antagonisté; GABA Antagonists; Male; Bicuculline; evokované potenciály; Evoked Potentials; implantované elektrody; krysa rodu Rattus; mozková kůra; Cerebral Cortex; zvířata; mužské pohlaví; Rats; záchvaty; potkani Wistar